2023
DOI: 10.1093/hr/uhad166
|View full text |Cite
|
Sign up to set email alerts
|

The parallel biosynthesis routes of hyperoside from naringenin in Hypericum monogynum

Yingying Wang,
Zhirong Cui,
Qianqian Li
et al.

Abstract: Hyperoside is a bioactive flavonoid galactoside in both medicinal and edible plants. It plays an important physiological role in the growth of flower buds. However, the hyperoside biosynthesis pathway has not been systematically elucidated in plants including its original source Hypericaceae. Our group found abundant hyperoside in the flower buds of Hypericum monogynum, thereby we sequenced its transcriptome to study the biosynthetic mechanism of hyperoside. After gene screening and functional verification, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that hyperoside also has potential functions such as inhibiting pancreatic lipase [ 3 ] and treating Alzheimer's disease [ 4 ]. To ensure the therapeutic effect of Huangshu Kui in clinical practice, it is necessary to quickly and sensitively detect the content of the active ingredient hyperoside in Huangshu Kui [ 5 ]. Traditional methods for detecting active ingredients in traditional Chinese medicine include chromatography, mass spectrometry, electrophoresis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that hyperoside also has potential functions such as inhibiting pancreatic lipase [ 3 ] and treating Alzheimer's disease [ 4 ]. To ensure the therapeutic effect of Huangshu Kui in clinical practice, it is necessary to quickly and sensitively detect the content of the active ingredient hyperoside in Huangshu Kui [ 5 ]. Traditional methods for detecting active ingredients in traditional Chinese medicine include chromatography, mass spectrometry, electrophoresis, etc.…”
Section: Introductionmentioning
confidence: 99%